Hormone-Dependent Regulation of Renin and Effects on Prorenin Receptor Signaling in the Collecting Duct - Lara, Lucienne S.; Gonzalez, Alexis A.; Hennrikus, Matthew T.; Prieto, Minolfa C. (Current Hypertension Reviews, 2022)
The production of renin by the principal cells of the collecting duct has widened our understanding of the regulation of intrarenal angiotensin II (Ang II) generation and blood pressure. In the collecting duct, Ang II increases the synthesis and secretion of renin by mechanisms involving the activation of Ang II type 1 receptor (AT1R) via stimulation of the PKCα, Ca2+, and cAMP/PKA/CREB pathways. Additionally, paracrine mediators, including vasopressin (AVP), prostaglandins, bradykinin (BK), and atrial natriuretic peptide (ANP), regulate renin in principal cells. During Ang II-dependent hypertension, despite plasma renin activity suppression, renin and prorenin receptor (RPR) are upregulated in the collecting duct and promote de novo formation of intratubular Ang II. Furthermore, activation of PRR by its natural agonists, prorenin and renin, may contribute to the stimulation of profibrotic factors independent of Ang II. Thus, the interactions of RAS components with paracrine hormones within the collecting duct enable tubular compartmentalization of the RAS to orchestrate complex mechanisms that increase intrarenal Ang II, Na+ reabsorption, and blood pressure.
Keywords: bradykinin